2020
DOI: 10.1371/journal.pone.0230254
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting severe grape downy mildew attacks using machine learning

Abstract: Grape downy mildew (GDM) is a major disease of grapevine that has an impact on both the yields of the vines and the quality of the harvested fruits. The disease is currently controlled by repetitive fungicide treatments throughout the season, especially in the Bordeaux vineyards where the average number of fungicide treatments against GDM was equal to 10.1 in 2013. Reducing the number of treatments is a major issue from both an environmental and a public health point of view. One solution would be to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…Bioclimatic indices were calculated starting from daily data on air temperature and precipitation, considering three different periods: (i) from November to January for the indices describing the weather conditions during overwintering (average of minimum, maximum and mean daily temperature), (ii) from November to March for monthly mean air temperature and cumulative precipitation, (iii) from April to October (monitoring period) for the bioclimatic indices describing the weather conditions in the interval from 14 to 7 days before the monitoring day or during the 7 days before the monitoring day. We considered these two time steps to identify the environmental conditions of the period during which the pathogen penetration into the host tissues was most probable (avg_14_7, avg_max_14_7, avg_ min_14_7, cum_rain_14_7) (Chen et al, 2020;Carisse et al, 2009;Barka et al, 2002).…”
Section: Variables Associated With Grapevine Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioclimatic indices were calculated starting from daily data on air temperature and precipitation, considering three different periods: (i) from November to January for the indices describing the weather conditions during overwintering (average of minimum, maximum and mean daily temperature), (ii) from November to March for monthly mean air temperature and cumulative precipitation, (iii) from April to October (monitoring period) for the bioclimatic indices describing the weather conditions in the interval from 14 to 7 days before the monitoring day or during the 7 days before the monitoring day. We considered these two time steps to identify the environmental conditions of the period during which the pathogen penetration into the host tissues was most probable (avg_14_7, avg_max_14_7, avg_ min_14_7, cum_rain_14_7) (Chen et al, 2020;Carisse et al, 2009;Barka et al, 2002).…”
Section: Variables Associated With Grapevine Diseasesmentioning
confidence: 99%
“…Because these pathogens may cause severe symptoms on grapevines at the beginning of infection, control strategies have focused on early treatments, even in integrated pest management (IPM), as prevention to stop the pathogen outbreak before its establishment. Applying fungicide treatments during the growing season remains the most common practice to control these diseases, from early spring onward, with differences between years due to weather conditions and to the geographic location of the vineyard (Chen et al, 2020;Lu et al, 2020;Molitor et al, 2016). However, concerns about the negative impact of chemicals on environmental and human health have resulted in restrictions to regulate fungicide use, such as the EU directives (i.e., Directive 1107/2009/EU) (Valdés-Gómez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning is a category of information science that trains the computer to execute tasks by recognizing patterns in massive datasets and using them to determine rules or algorithms that optimize task achievement [24]. It has been reported that machine learning is beneficial to the discovery of predictive biomarkers and diagnosis of GDM [7,[25][26][27]. Support vector machine (SVM) is a practical machine learning model and has been confirmed to be useful classifiers in all kinds of fields, including face recognition, handwritten digit recognition, text classification, and bioinformatics [28].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ascertain high-risk periods for primary infections and time of fungicidal sprays, several weather-driven models have been proposed in different countries (Tran Manh Sung et al, 1990;Hill, 2000;Park et al, 1997). A new machine learning algorithms model for predicting the probability of high incidence was developed by Chen et al (2020) and proposed the risk of grapes downy mildew at bunch maturity stage due to rainfall and temperatures in Bordeaux region of south western France. An advantage of this mathematical tool is the intrinsic relationship with other tools like disease progress curves and computer simulations because important components of disease dynamics can be modelled by using growth models that latter could be linked and simulated using computer programs (Mersha and Hau, 2008).…”
Section: Introductionmentioning
confidence: 99%